A new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the Ishizuchi range, Shikoku, Japan - Murányi, Dávid; Gamboa, Maribet; Watanabe, Kozo (Zootaxa, 2020)
A new species of the genus Protonemura Kempny, 1898 (Plecoptera: Nemouridae: Amphinemurinae) is described from the Ishizuchi Range of Shikoku Island, Japan, based on the male, female and Co1 sequences. Protonemura shimizui Murányi & Gamboa sp. n. belongs to the P. orbiculata species group sensu Shimizu, 1998. The new species appears to be limited to the higher elevations of the Ishizuchi Range. Faunistic survey of the high elevation rheocrenes of the Ishizuchi Range is also presented.